Making Tempe From Peanuts (Arachis Hypogaea) As An Alternative To Soybeans (Glycine Max L.) In Making Tempe: Making Tempe From Peanuts - Khairunisa Khairunisa; Aniza Haridha Zain (Jurnal Agritechno, 2025)
Tempe is a local Indonesian processed food, usually made from soybeans. Peanuts are used as an alternative to soybeans. The purpose of this study was to develop peanut-based tempe as an alternative to soybeans. Tempe is made with the fermentation fungi R. oligosporus or R. oryzae in soybeans. The research was both observational and experimental. The observational study included observations of the tempe-making process at the Tempe Purba P. Heri factory, while the experimental study included a remake with peanuts. The experimental results showed differences in the fermentation process between soybean and peanut tempeh, particularly in the fermentation time for soybeans and peanuts. The observed soybean tempeh production process took 72 hours, while the peanut-based tempeh production process took 8 hours. Peanut tempeh had a stronger flavor and aroma than soybean tempeh.